IN VITRO IMPROVEMENT OF CHARACTERS IN ROSA SPP. THROUGH COLCHICINE - M. M. Q. Baig; T. Ahmad1; I. A. Hafiz; N. A. Abbasi; M. J. Tareen (Journal of Animal and Plant Sciences, 2016)
Flower size and color variation are the main attributes in the floriculture industry that affect the consumers demand. Rosa gruss an teplitz  and Rosa centifolia are the fragrant rose species  known for their  wonderful aesthetic beauty. However, they are limited in use due to their small sized flowers and no color variegation. In order to  improve  characters in rose species, shoot tips taken from micropropagated plants were incubated for three different periods of 5, 7 and 11 days in MS medium containing different levels (0,100, 150, 300 and 450 mg l-1) of colchicine. Rosa gruss an teplitz and Rosa centifolia yielded maximum  plant height (15.12 and 17.23cm), number of nodes (4.80 and 6.93), internodal distance (3.15 and 2.48 cm), leaf area (5.26 and 10.50 cm2)   and flower size (6.24 and 5.78cm) respectively at colchicine level of 450 mg l-1 with incubation period of 11days. Colchicine also induced variegation and variation in flowers of Rosa gruss an teplitz. Genetic variation was analyzed and dendrogram was developed to assess the relationship with parent material.  The findings of this work add to the ongoing efforts to improve the characters through induction of mutation in rose flowers.
Keywords: Rosa gruss an teplitz; Rosa centifolia; colchicine; RAPD; variation